Identification of Phonology-Related Genes and Functional Characterization of Broca’s and Wernicke’s Regions in Language and Learning Disorders - Unger, Nina; Heim, Stefan; Hilger, Dominique I.; Bludau, Sebastian; Pieperhoff, Peter; Cichon, Sven; Amunts, Katrin; Mühleisen, Thomas W. (Frontiers in Neuroscience, 2021)
Impaired phonological processing is a leading symptom of multifactorial language and learning disorders suggesting a common biological basis. Here we evaluated studies of dyslexia, dyscalculia, specific language impairment (SLI), and the logopenic variant of primary progressive aphasia (lvPPA) seeking for shared risk genes in Broca’s and Wernicke’s regions, being key for phonological processing within the complex language network. The identified “phonology-related genes” from literature were functionally characterized using Atlas-based expression mapping (JuGEx) and gene set enrichment. Out of 643 publications from the last decade until now, we extracted 21 candidate genes of which 13 overlapped with dyslexia and SLI, six with dyslexia and dyscalculia, and two with dyslexia, dyscalculia, and SLI. No overlap was observed between the childhood disorders and the late-onset lvPPA often showing symptoms of learning disorders earlier in life. Multiple genes were enriched in Gene Ontology terms of the topics learning (CNTNAP2, CYFIP1, DCDC2, DNAAF4, FOXP2) and neuronal development (CCDC136, CNTNAP2, CYFIP1, DCDC2, KIAA0319, RBFOX2, ROBO1). Twelve genes showed above-average expression across both regions indicating moderate-to-high gene activity in the investigated cortical part of the language network. Of these, three genes were differentially expressed suggesting potential regional specializations: ATP2C2 was upregulated in Broca’s region, while DNAAF4 and FOXP2 were upregulated in Wernicke’s region. ATP2C2 encodes a magnesium-dependent calcium transporter which fits with reports about disturbed calcium and magnesium levels for dyslexia and other communication disorders. DNAAF4 (formerly known as DYX1C1) is involved in neuronal migration supporting the hypothesis of disturbed migration in dyslexia. FOXP2 is a transcription factor that regulates a number of genes involved in development of speech and language. Overall, our interdisciplinary and multi-tiered approach provided evidence that genetic and transcriptional variation of ATP2C2, DNAAF4, and FOXP2 may play a role in physiological and pathological aspects of phonological processing.